A community approach to physiotherapy - P. J. Wallner; A. Stewart (AOSIS, 1994)
This paper explores the reasons for the introduction of a community component to the current physiotherapy curriculum. The development of the community component of the course is outlined as are the student attitudes towards this development. The necessity for this trend to continue in the interests of meeting the rehabilitative needs of all the communities in South Africa is highlighted.